Тhe prevalence and structure of tooth-jaw anomalies in children of contaminated areas of the ecosystem of the Upper Tysa region - Потапчук, Анатолій Мефодійович; Мельник, Володимир Семенович; Горзов, Людмила Федорівна; Алмаші, Василь Миколайович (Actual Dentistry, 2019)
Resume. The article presents the data of the prevalence and structure of tooth-jaw anomalies in Upper Tysa region children and an analysis of the structure of tooth-jaw anomalies depending on the area of residence. Methods. A dental examination of 360 children aged 15–18, 198 (55 %) boys and 162 (45 %) Girls of Upper Tysa region was conducted in each geographical and natural-climatic region. Results. The analysis of the prevalence of dental anomalies in children living in different biogeochemical zones has shown that much more commonly found in children living in the foothills zone. In the low zone, the anomalies of the dental rows is 39.66±4.34 %, the anomalies of the individual teeth are diagnosed in 36.42±3.21 % and 30.43±3.27 % in the anomalies of the occlusion. Anomalies of individual teeth are most often found in the lowland zone in Romania 36.42±3.21 %, dental rows anomalies in the foothill zone 40.25±4.53 %, and anomalies of the occlusion in the mountain zone of 31.13±3.17 % in Transcarpathia. In the lowland biogeochemical zone among the anomalies of bite, a deep bite (40.47±4.04 %) was found in children of Transcarpathia and distal bite (37.26±4.53 %) in children of Romania more often. The frequency of anterior maxillary overlappiness in children of Transcarpathia is 27.73±1.51 %, whereas in children of Hungary 23.08±1.26 %. The prevalence of severe bite dysfunctions (with a DAI score of 31–35 points) was significantly more pronounced among Romanian children (16.59±1.93 %) and Transcarpathia (15.71±1.84 %). In the group of very serious pathologies (DAI ≥ 36 points) the lowest number was found among children in Hungary – 8.61±1.79 %. Conclusions. The conducted researches have established a high prevalence of tooth-jaw anomalies among children living in the Upper Tysa region, primarily in the foothills and lowland biogeochemical zones. According to the criteria of the DAI index, obligatory orthodontic care requires 10–11 % of children in the Upper Tysa region, which must be taken into account when developing program and conducting a set of preventive measures and treatment of orthodontic pathology in this category of children. Key words: teeth and jaw anomalies, children, biogeochemical zones, ecosystem pollution, index DAI.